Strategic Approaches to Islamic Education in Madrasah An-Nikmah Al-Islamiyah, Cambodia - Purba, Edi Ikhwansyah; Harfiani, Rizka (Journal of English Language and Education, 2025)
Learning Islamic religious education plays a significant role in shaping students' moral character, particularly in fostering mutual respect for differing opinions. This study aims to analyze the strategic approaches employed in Islamic religious education at Madrasah An-Nikmah Al-Islamiyah in Phnom Penh, Cambodia, within the context of a multicultural student body comprising diverse ethnic backgrounds. Utilizing a qualitative descriptive methodology, the research involved in-depth interviews, data collection from participants, and thorough data analysis and interpretation. The findings reveal four key strategies: the integration of local cultural values into the curriculum, the use of technology-enhanced learning media, the implementation of active learning methodologies, and the cultivation of Islamic character education to deepen students’ understanding of Islamic principles and reinforce moral development. Despite notable progress, challenges such as limited culturally relevant teaching materials and language barriers remain. The study concludes that the adoption of innovative and adaptive teaching strategies is crucial for delivering effective and culturally responsive Islamic education in diverse learning environments.